Inactivation kinetics of peroxidase in zucchini (Cucurbita pepo L.) by heat and UV-C radiation - Neves, Filipa I. G. (2013)
The effect of traditional thermal water blanching, or its combination with a UV-C radiation pre-treatment (11 J/m2), on the inactivation kinetics of peroxidase in zucchini (Cucurbita pepo L.) was carried out in the temperature range of 80 to 98 °C, and up to 3 min of processing time. Peroxidase inactivation started being noticed only at temperatures around 85 °C. For both treatments, the inactivation kinetics followed a first order reaction with the Arrhenius model describing the temperature dependence of the reaction rate. The obtained kinetic parameters (kHeat 89.6 °C = 7.37 × 10− 7 ± 3.47 × 10− 7 min− 1 and Ea Heat = 925 ± 69 kJ mol− 1; kHeat 89.6 °C + UV-C = 2.42 × 10− 5 ± 6.58 × 10− 6 min− 1 and Ea Heat + UV-C = 596 ± 48.8 kJ mol− 1) showed that UV-C radiation had a significant contribution to increase the peroxidase degradation rate. These results will help to design new pre-processing conditions for the production of frozen zucchini, using less severe thermal treatments and attempt to minimize quality losses.